2005
DOI: 10.1111/j.1439-0418.2005.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of detoxifying enzymes to pyrethroid resistance in a resistant strain of Helicoverpa armigera

Abstract: The relative contribution of oxidases and esterases to pyrethroid resistance was studied in a YS-FP strain of Helicoverpa armigera from China. The YS-FP strain was derived from a field-collected strain (YS) by 16 generations of selection with a mixture of fenvalerate and phoxim. Compared with the YS strain, the YS-FP strain showed 1850-to >7140-fold resistance to four ester-bonded phenoxybenzyl alcohol pyrethroids (fenvalerate, deltamethrin, cypermethrin and cyhalothrin), >205-fold resistance to a non-ester ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…The degree of P450-mediated resistance to pyrethroids in the YS-FP strain from China was found to depend on the nature of the alcohol moiety in the pyrethroid structure (Yang et al, 2005). Resistance to pyrethroids in the CMR strain from China was also mainly due to enhanced oxidative metabolism, and substitution of the phenoxybenzyl group found in the alcohol moiety of most commercial pyrethroids with a polyfluorobenzyl group (eg in tefluthrin, benfluthrin and transfluthrin) overcame most of the resistance (Tan and McCaffery, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…The degree of P450-mediated resistance to pyrethroids in the YS-FP strain from China was found to depend on the nature of the alcohol moiety in the pyrethroid structure (Yang et al, 2005). Resistance to pyrethroids in the CMR strain from China was also mainly due to enhanced oxidative metabolism, and substitution of the phenoxybenzyl group found in the alcohol moiety of most commercial pyrethroids with a polyfluorobenzyl group (eg in tefluthrin, benfluthrin and transfluthrin) overcame most of the resistance (Tan and McCaffery, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Enhanced metabolism of the insecticide by detoxifying enzymes such as cytochrome P450-dependent monooxygenases, glutathione-Stransferases and carboxylesterases is responsible for a significant proportion of this resistance (Bues et al, 2005;Yang et al, 2005;Ahmad et al, 2006;Ugurlu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58] Whether this geographic variation in the strength of the associations reflects genetic differences among populations or methodological differences among investigators is moot, although some effect of genetic differences seems likely. Esterases seem to be responsible for only a few-fold resistance in Chinese populations, 54,55) whereas much higher resistance factors have been attributed to the esterases in some of the other populations. 39,42) Similarly the increase in esterase activity in the Chinese resistant strains is only a few-fold but in at least one Australian study the corresponding figure is reported to be as much as 50-fold.…”
Section: Heliothine Resistance To Spsmentioning
confidence: 99%
“…The association is particularly strong in data for populations from Australia, [39][40][41][42] south and southeast Asia [43][44][45][46][47][48][49][50][51] and central Africa 52,53) and is also significant in Chinese populations, 46,54,55) although it has not been found in west African populations. [56][57][58] Whether this geographic variation in the strength of the associations reflects genetic differences among populations or methodological differences among investigators is moot, although some effect of genetic differences seems likely.…”
Section: Heliothine Resistance To Spsmentioning
confidence: 99%